The Attachment of Demonstrators to Institutional Politics: Comparing LGBTIQ Pride Marches in Argentina and Chile - Somma, Nicolás M. (2020)
Focusing on LGBTIQ demonstrations in Argentina and Chile, we study protesters' attachment to institutional politics, defined as their emotional and attitudinal connection with the political system. We show that Argentine LGBTIQ demonstrators are on average more attached to institutional politics than Chilean ones. This can be explained neither by differences between Argentines and Chileans in general, nor by demonstrators' individual characteristics. Instead, expanding the political process model, we argue that achieving a substantial part of the LGBTIQ agenda in Argentina, and limited success in Chile, contributed to build a stronger attachment to the political system among Argentine LGBTIQ demonstrators than their Chilean counterparts.